Incidence of epidural spread after Chayen’s approach to lumbar plexus block: a retrospective study - Rosanò,Elisabetta (2020)
Abstract Background and objectives: The lumbar plexus block (LPB) is a key technique for lower limb surgery. All approaches to the LPB involve a number of complications. We hypothesized that Chayen's approach, which involves a more caudal and more lateral needle entry point than the major techniques described in the literature, would be associated with a lower rate of epidural spread. Method: We reviewed the electronic medical records and chart of all adult patients who underwent orthopedic surgery for Total Hip Arthroplasty (THA) and hip hemiarthroplasty due to osteoarthritis and femoral neck fracture with LPB and Sciatic Nerve Block (SNB) between January 1, 2002, and December 31, 2017, in our institute. The LPB was performed according to Chayen’s technique using a mixture of mepivacaine and levobupivacaine (total volume, 25 mL) and a SNB by the parasacral approach. The sensory and motor block was evaluated bilaterally during intraoperative and postoperative period. Results: A total number of 700 patients with American Society of Anesthesiologists (ASA) physical status I to IV who underwent LPB met the inclusion criteria. The LPB and SNB was successfully performed in all patients. Epidural spread was reported in a single patient (0.14%;p < 0.05), accounting for an 8.30% reduction compared with the other approaches described in the literature. No other complications were recorded. Conclusions: This retrospective study indicates that more caudal and more lateral approach to the LPB, such as the Chayen’s approach, is characterized by a lower epidural spread than the other approach to the LPB.